1998
DOI: 10.1088/0022-3727/31/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation rate of a sample-induced thermal fluctuating field in the tip of a probe microscope

Abstract: Fluctuation electrodynamics was used as a basis to obtain an expression for the dissipation power of a thermal electromagnetic field of a heated plane sample in the tip of a probe microscope, as a function of the value of a gap between them. We have shown that the energy dissipation rate is inversely proportional to the tip-sample distance cubed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…The insights obtained in this work are especially pertinent with regard to recent developmemts in scanning thermal microscopy [34,35]. It has been argued that the tip of a thermal microscope operating in ultrahigh vacuum is sensitive to the near-field energy density above the sample; experiments along this direction are presently underway [36].…”
Section: Discussionmentioning
confidence: 87%
“…The insights obtained in this work are especially pertinent with regard to recent developmemts in scanning thermal microscopy [34,35]. It has been argued that the tip of a thermal microscope operating in ultrahigh vacuum is sensitive to the near-field energy density above the sample; experiments along this direction are presently underway [36].…”
Section: Discussionmentioning
confidence: 87%
“…It is known that the radiative heat flux between two bodies [10,11,12,13,14,15,16,17,18,19] can be dramatically enhanced when their separation distance becomes smaller than 10µm. It was found that evanescent waves yield the leading contribution to the heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…The electric dipole moment of a sphere with radius R and dielectric constant ǫ r is generally assumed to give the leading contribution [18,19,20,21,22,23,24,25] because it varies like (R/λ) 3 whereas the next term in the Mie expansion varies as (R/λ) 5 (λ is the wavelength in vacuum) [34]. In this work, we will show that the interaction between the magnetic dipole and the large magnetic fields in the near field may give the dominant contribution to the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The right-hand side of this equation still is written in a manner which shows that it does not depend on the choice of the particular coordinate system used for its evaluation, as the trace over the product of the polarization tensor and the correlation tensor manifestly remains invariant under coordinate transformations. When adopting a coordinate system in which the tensor α E (ω) is diagonal, with diagonal elements α E k (ω), this expression (3) takes the more familiar form [21][22][23][24] …”
Section: The Basic Principlementioning
confidence: 99%
“…If all elements α E k (ω) are equal, as in the case of a nanosphere, the integrand simply is proportional to the trace of the correlation tensor, i.e., to the spectral energy density which is the case considered usually [21][22][23][24]. If, however, the elements α E k (ω) differ significantly from each other, the dissipated power can be dominated by individual components W E kk (r, r, ω).…”
Section: The Basic Principlementioning
confidence: 99%